Analisis Pengaruh Komunikasi, Disiplin Kerja, dan Motivasi terhadap Kinerja Pegawai Badan Pusat Statistik Kabupaten Probolinggo - Totok Harianto (Fakultas Ekonomi dan Bisnis Islam, 2018)
In order to support bureaucratic reform within the central statistical agency of probolinggo district, it is demanded human resources that have good performance. From some of the phenomenon observed can be seen that communication, work discipline and motivation as a variable that has an influence on the performance of the Central Statistics Agency employees Probolinggo.The purpose of this research are: (1) Analyze and describe the influence of simultaneous (variant) of communication, work discipline, and motivation toward employee performance of Central Bureau of Statistics of Probolinggo Regency. (2) Analyze and describe the influence individually (partial) of communication, work discipline, and motivation to the performance of employees of Central Bureau of Statistics of Probolinggo Regency. (3) Analyze and describe which variable is the biggest influence between communication, work discipline, and motivation to employee performance of Central Bureau of Statistics of Probolinggo Regency.The sample in this study is a population of 35 people from all employees of the Central Bureau of Statistics of Probolinggo Regency. Analysis technique used duntuk know variable (X) to variable not free (Y) by using doubled linear regression.The results of this study indicate that: (1) communication, work discipline, and motivation have influence in the significant increase of work equal to 79,9%. While the rest of 20.1% is influenced by other variables that are not examined. (2) communication, work discipline, and motivation together affect performance. This can be indicated by the F test value of 0.000 smaller 0.05. (3) the variables of communication, work discipline, and motivation affect each performance. This is indicated by the significance of the t test of each variable less than 0.05. (4) work discipline variable has a dominant influence on performance. This is indicated by the beta value of 0.468 is greater among other variables